THE IMPORTANCE OF MULTIMEDIA AND MOBILE APPLICATIONS IN TEACHING FOREIGN LANGUAGES - Botirov Doniyor; Olimjonova Asalabonu Ziyodjonovna (American Journals, 2023)
Multimedia is an effective and engaging tool that can be used to improve vocabulary acquisition for all learners and engage them in the learning process. The development of modern society occurs in the era of informational technologies and characterized by the use of information technology tools in many areas of human activities, including in the field of education. The rational combination of education means with the modern information and computer technologies (ICT) is one of the possible ways for solving the problem of educational modernization.This article explains the role of multimedia in foreign language teaching and the importance of mobile applications in the effective organization of leisure time. Moreover, the most popular mobile apps and their summaries are given in this paper.
Keywords: Multimedia, solving the problem ,specific tasks, knowledge ,language, grammar, reading comprehention,speaking,pronunciation,apps,e-resources,lessons,independent development, presentation, games, devices.